2012
DOI: 10.3897/phytokeys.10.2297
|View full text |Cite
|
Sign up to set email alerts
|

Eriocaulon madayiparense (Eriocaulaceae) – A new species from the foot hills of the Western Ghats of India

Abstract: Eriocaulon madayiparense Swapna, Rajesh, Manju & Prakashkumar, sp. nov. is described and illustrated from the Madayipara, a lateritic hillock in the midland of Kannur District of Kerala. The species is allied to Eriocaulon eurypeplon Koernicke, in its two free male and female sepals, female sepals being keeled and acute and not exceeding the floral bracts, acuminate leaf apex and setiform seed appendages appearing in vertical rows, but differs mainly in having yellow seeds with solitary appendage arising from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…After the comprehensive taxonomic revision of the family by Ruhland (), Ansari and Balakrishnan () revised the genus Eriocaulon for India and recognized 80 species of which 68 are from a Peninsular Indian region showing the greatest diversity of species in that area. Subsequently a few more species such as E. epedunculatum Potdar et al (Yadav et al ), E. baramaticum Shimpale et al (), E. wayanadense Vivek et al (), E. malabaricum Pradeep et Nampy (Nampy et al ), E. pykarense Nampy et Manudev (Nampy et al ), E. madayiparense Swapna et al (), E. cheemenianum Biju et al (), E. kannurense Sunil et al (), and E. gopalakrishnanum Rashmi and Krishnakumar () have been described from Peninsular India. Nair () reported the taxonomic significance of seed coat morphology in Eriocaulon and Giulietti et al () used scanning electron microscopy to study and compare seed‐coat sculptural patterns of various genera of the family; and this character facilitated differentiation of closely related species (Phillips , , , Zhang , Davies et al ).…”
Section: Eriocaulon Vandaanamense Sunil Ratheesh Et Sivadasan Sp Nomentioning
confidence: 99%
“…After the comprehensive taxonomic revision of the family by Ruhland (), Ansari and Balakrishnan () revised the genus Eriocaulon for India and recognized 80 species of which 68 are from a Peninsular Indian region showing the greatest diversity of species in that area. Subsequently a few more species such as E. epedunculatum Potdar et al (Yadav et al ), E. baramaticum Shimpale et al (), E. wayanadense Vivek et al (), E. malabaricum Pradeep et Nampy (Nampy et al ), E. pykarense Nampy et Manudev (Nampy et al ), E. madayiparense Swapna et al (), E. cheemenianum Biju et al (), E. kannurense Sunil et al (), and E. gopalakrishnanum Rashmi and Krishnakumar () have been described from Peninsular India. Nair () reported the taxonomic significance of seed coat morphology in Eriocaulon and Giulietti et al () used scanning electron microscopy to study and compare seed‐coat sculptural patterns of various genera of the family; and this character facilitated differentiation of closely related species (Phillips , , , Zhang , Davies et al ).…”
Section: Eriocaulon Vandaanamense Sunil Ratheesh Et Sivadasan Sp Nomentioning
confidence: 99%
“…Although the Food and Drug Administration (FDA) has not approved the use of any antibiotics in U.S. shrimp aquaculture, other nations use various antibiotics in their shrimp aquaculture practices [3]. Multiple studies have demonstrated the presence of antimicrobial residues, including β-lactam, erythromycin, sulfonamide, and tetracycline, in samples of shrimp sourced from aquaculture operations in Southeast Asia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The species are mostly acaulescent herbs with a monoecious capitate inflorescence. Ansari and Balakrishnan (2009) reported 80 species from India, but several new taxa have subsequently been added from India bringing the total number to 112 (Shimpale et al 2009, Shimpale and Yadav 2010, Vivek et al 2010, Nampy et al 2011, Biju et al 2012, Swapna et al 2012, Sunil et al 2013, 2014, Rashmi and Krishnakumar 2014, Manudev et al 2015, Sunil and Naveen Kumar 2015, Anto and Reshma 2017, Darshetkar et al 2017, Naveen Kumar et al 2017, Paithane et al 2017, Chandore et al 2019, Khanna and Kumar 2019, Francis et al 2020.…”
Section: Introductionmentioning
confidence: 99%